A Review on the Progress and Prospects of Dengue Drug Discovery Targeting NS5 RNA- Dependent RNA Polymerase - Maddipati, Venkatanarayana C.; Mittal, Lovika; Mantipally, Manohar; Asthana, Shailendra; Bhattacharyya, Sankar; Gundla, Rambabu (Current Pharmaceutical Design, 2020)
Dengue virus (DENV) infection threatens the health and wellbeing of almost 100 million people in the world. Vectored by mosquitoes, DENV may cause a severe disease in human hosts called Dengue hemorrhagic fever (DHF)/Dengue shock syndrome (DSS), which is not preventable by any known drug. In the absence of a universally-accepted vaccine, a drug capable of inhibiting DENV multiplication is an urgent and unmet clinical need. Here we summarize inhibitory strategies by targeting either host biochemical pathways or virus-encoded proteins. A variety of approaches have been generated to design Directly-acting anti-virals or DAAs targeting different DENV proteins, with diverse success. Among them, DAAs targeting genome replicating viral enzymes have proven effective against many viruses including, Human Immuno-deficiency Virus and Hepatitis C Virus. DAAs may be derived either from existing compound libraries of novel molecules and plant secondary metabolites or devised through Computer-aided Drug design (CADD) methods. Here, we focus on compounds with reported DAA-activity against the DENV RNA-dependent RNA polymerase (RdRp), which replicate the viral RNA genome. The structure-activity relationship (SAR) and toxicity of the natural compounds, including secondary plant metabolites, have been discussed in detail. We have also tabulated novel compounds with known anti-RdRp activity. We concluded with a list of DAAs for which a co-crystal structure with RdRp is reported. Promising hit compounds are often discarded due to poor selectivity or unsuitable pharmacokinetics. We hope this review will provide a useful reference for further studies on the development of an anti-DENV drug.
Keywords: directly-acting anti-viral